DAMPAK GAYA KELEKATAN ORANG TUA DAN STIGMA DIRI TERHADAP INTENSI MENCARI BANTUAN REMAJA AKHIR - Arista Sabilla, Rizka; Dian Ariana, Atika (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Help-seeking intentions are antecedents of adolescents' decisions to seek help. The existence of barriers to accessing help lowers adolescents' intention, which results in low utilization of health services. Therefore, this study aims to determine the impact of parental attachment style and self-stigma on late adolescents' help-seeking intentions. The research design used quantitative methods, involving 172 participants aged 18–21 years. The data collection process applied the self-report questionnaire survey method, with measuring instruments such as the General Help-seeking Questionnaire, Self Stigma of Seeking Help Scale, and The Inventory of Parent and Peer Attachment-Revised. The data analysis method was applied with the covariate analysis method on Jamovi software version 2.3.28. Covariate analysis of parental attachment style with help-seeking intentions showed significant results, while the impact of self-stigma on help-seeking intentions showed insignificant results. Secure attachment style had the highest help-seeking intention, followed by anxious attachment style, and avoidant attachment style had the lowest help-seeking intention.